Private and Public Patriarchies: A Sylvia Walby-Inspired Analysis of Jennifer Saint's Ariadne (PANOPTICON: Journal of English Studies, 2025)
This study examines the patriarchal structures in Jennifer Saint's novel Ariadne through Sylvia Walby's theoretical framework, which distinguishes between private and public patriarchy. Employing a qualitative method, this research analyzes textual data to reveal how these interconnected systems shape the experiences of female characters like Ariadne, Phaedra, and Pasiphaë. The findings demonstrate that patriarchal control within the household (private) and through state and religious institutions (public) systematically limits women's roles, silences their voices, and erases their agency. This study underscores the value of feminist myth-retellings in critiquing enduring gender inequalities, highlighting Ariadne's significance as a contemporary literary intervention